PENGEMBANGAN MEDIA BACA DIGITAL BERBASIS E-BOOK UNTUK MENINGKATKAN MINAT BACA SISWA KELAS III SDN MOJOROTO 4 - Daffa Bhadra Thaariq Untaryo; Erwin Putera Permana; Agus Widodo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a digital reading media based on e-book as a learning tool to enhance the reading interest of third-grade students at SDN Mojoroto 4, Kediri City. The research employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 28 students. The instruments used included expert validation questionnaires, student response questionnaires, and a reading interest questionnaire validated by a literacy expert. The validation results indicated that the media achieved a validity level of 90%, categorized as highly valid. The practicality of the media, based on student responses, reached 94.5%, while its effectiveness was shown by a 30% increase in reading interest scores from pretest to posttest. Based on these findings, the developed digital reading media based on an e-book is considered highly valid, highly practical, and highly effective, and is suitable for use in primary school reading instruction.